Photocatalytic reduction of iodine in radioactive waste water using maghemite and titania nanoparticles in PVA-alginate beads - Majidnia, Zohreh (Taiwan Institute of Chemical Engineers, 2015)
The presence of iodine ions in nuclear waste water is a major concern due to its high level of toxicity. In this study three different types of beads were prepared; i) maghemite (?-Fe2O3) PVA-alginate beads, ii) titania (TiO2) PVA-alginate and iii) combined ?-Fe2O3 and TiO2 nanoparticles embedded in PVA-alginate defined as maghemite and titania PVA-alginate beads respectively. These beads were used in batch sorption experiments for iodine ions removal from radioactive waste water under sunlight. The combined ?-Fe2O3 and TiO2 nanoparticles embedded in PVA-alginate was able to remove the I(1) rapidly with maximum efficiency. Results revealed that I(1) removal was enhanced under sunlight irradiation and XPS findings proved that I(1) was reduced to I(0) indicating that photocatalytic process has occurred. Maximum removal of I(1) was achieved at maximum pH of 8. The maghemite and titania PVA-alginate beads were robust; losing only 13% of its photocatalytic properties after recycling for seven times. Kinetic studies illustrated that I(1) removal followed the pseudo-second-order model with the R2 > 0.99.